PONDOK PESANTREN MODERN: POLITIK PENDIDIKAN ISLAM DAN TANTANGAN IDENTITAS MUSLIM - Manshuruddin, Manshuruddin (Jurnal Ilmiah Al-Hadi, 2019)
Pesantren is the oldest Islamic education institution in Indonesia. At first, the pesantren was known as a traditional educational institution that was taught in surau, prayer rooms, mosques, or the foyer of a teacher using the bandongan and sorogan methods. The books studied in Jurisprudence are generally written in Arabic without lines (harakat) usually called bare books (without harakat) or yellow books (because the paper is yellowish in color). Later, along with the times and advances in science and technology (science and technology), as well as the enactment of the National Education System Law, education in pesantren has been more formulated, in essence there has been an update or modernization of the pesantren education system including: a) developing curriculum in accordance times, b) complementing the means of supporting the learning process, c) developing the santes lifeskill, d) providing a vehicle for self-actualization in the community. Facing the era of globalization which has an impact on various changes both in the economic and socio-cultural fields, the Islamic boarding school is required to respond adaptively and even innovatively with a balanced knowledge of both diniyah and madiyah. So in facing the challenges of the times, pesantren must also always hold the principles of renewal while upholding the values of Islamic teachings, having guided freedom, being able to self-regulate, having a high sense of togetherness, respecting parents and teachers, love of science , independent and simple as an effort to maintain the existence and Islamic identity of its adherents.